The Silver Swan and Her Stroke: First Songs as Last Songs - Weeks, Kaja (Ars Medica, 2017)
This is a view of a massive stroke followed by rare communications through singing and vocalizations between an elegant lady born by the Baltic Sea almost 100 years ago and her daughter (the author). A reflective true account with story-like narration, it conveys the intersection of a musically rhythmic but "pitch deaf" mother and classically-trained singer daughter at their final crossroads. The stunning scene of hearing her mother, unable to speak, but singing "with full power and nuance, like a glorious Wagnerian soprano," has the author first considering the extrordinary plasticity of the brain, and then, as a daughter, the poignant meaning of her mother's sounds, who like the Silver Swan, "sung her first and last, and sung no more."